2010
DOI: 10.1111/j.1365-2230.2009.03441.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intrauterine ischaemia-reperfusion injury on rat skin

Abstract: Lipid peroxidation has an important role in intrauterine ischaemia-reperfusion-induced fetal skin damage in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
2
2
0
Order By: Relevance
“…We recently showed that fetal skin is vulnerable to intrauterine I/R injury when lipid peroxidation values increased after I/R injury. 10 Consistent with our previous work, we found in the current study that levels of TBARS, MPO and NO increased significantly in fetal skin tissue after intrauterine I/R injury. Our findings suggest that IR injury to fetal skin, causing an increase in TBARS levels, could also affect DNA, 17 and potentially cause conditions such as vitiligo, 18 lichen planus, 19 atopic dermatitis, 20 rosacea, 21 skin cancer 22 and ageing 22 in which reactive oxygen species have been shown to be involved.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We recently showed that fetal skin is vulnerable to intrauterine I/R injury when lipid peroxidation values increased after I/R injury. 10 Consistent with our previous work, we found in the current study that levels of TBARS, MPO and NO increased significantly in fetal skin tissue after intrauterine I/R injury. Our findings suggest that IR injury to fetal skin, causing an increase in TBARS levels, could also affect DNA, 17 and potentially cause conditions such as vitiligo, 18 lichen planus, 19 atopic dermatitis, 20 rosacea, 21 skin cancer 22 and ageing 22 in which reactive oxygen species have been shown to be involved.…”
Section: Discussionsupporting
confidence: 93%
“…There are few data describing the effect of intrauterine I/R injury on fetal skin. We recently showed that fetal skin is vulnerable to intrauterine I/R injury when lipid peroxidation values increased after I/R injury . Consistent with our previous work, we found in the current study that levels of TBARS, MPO and NO increased significantly in fetal skin tissue after intrauterine I/R injury.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations